Metadata and semantics research : 10th International Conference, MTSR 2016, Göttingen, Germany, November 22-25, 2016, proceedings /: 10th International Conference, MTSR 2016, Göttingen, Germany, November 22-25, 2016, proceedings. (2016) - Unknown
No abstract available